The genome sequence of a bark-dwelling beetle, Silvanus unidentatus (Olivier, 1790) [version 1; peer review: 2 approved] - Mark G. Telfer; Maxwell V. L. Barclay; Michael F. Geiser; Toby Turner (Wellcome Open Research)
We present a genome assembly from a specimen of Silvanus unidentatus (bark-dwelling beetle; Arthropoda; Insecta; Coleoptera; Silvanidae). The genome sequence has a total length of 187.15 megabases. Most of the assembly (84.24%) is scaffolded into 7 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 17.15 kilobases in length. Gene annotation of this assembly on Ensembl identified 11,364 protein-coding genes.